Waste Bank Loose Part Sebagai Alat Edukasi Pembelajaran Steam Yang Aman Dan Ramah Lingkungan Di Paud Aisyiyah Al Amin Surakarta - Dina Pertiwi Ajie; Sari Pitria Ayu; Rizky Hanadya Tri Kusuma; Safira Meida Putri (CV. Multi Kreasi Media, 2023)
In this pandemic transition era as a teacher we are required to overcome learning loss when children learn from home. Therefore, Loose Part media in STEAM learning is very helpful for children so that their developmental aspects can be achieved according to their age (Nurjanah, 2020). Loose Part media, which has many varieties around a safe and environmentally friendly environment for AUD, is the right medium today to achieve 6 aspects of child development (Kusuma dkk, 2022). Therefore, the existence of